BREAK EVENT POINT ANALYSIS ON BROILER FARMS OF OKU REGENCY - Ayugustin Ayugustin; Fifian Permata Sari Fifian; Yetty Oktarina (International Journal of Social Science, 2022)
This study aims to analyze the income and break-even point of broiler farming in OKU Regency. The research method used is a survey method and the sampling method used is a saturated sampling method with a total sample of 8 broiler breeders spread across Lubuk Raja District and Lubuk Batang District, OKU District. The study was carried out from February to May 2022. The research data was processed using a mathematical equation to calculate the income of broiler business and the break-even point of broiler business in OKU Regency, then to analyze the break-even point of broiler business, it was analyzed using BEP analysis. The results showed that The average income of broiler farming in OKU Regency is Rp. 57.167.110/year. Break Even Point (BEP) in broiler chicken business production is 38,641.97 heads/year, BEP price is IDR 18.683,33/kg in a year and BEP income is IDR 752.291/head/year.